Pengaruh Brand Love Terhadap Purchase Decision Oreo pada Generasi Z di Kota Jayapura - Indra Eka Wardana Toii (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of brand love on purchase decisions for Oreo products among Generation Z in Jayapura City. Brand love, as a form of emotional attachment between consumers and brands, is seen as an important factor influencing purchasing behavior, especially among the younger generation, who are known to be responsive to brand identity, emotional experiences, and digital marketing activities. Although Oreo is a global brand with a high level of brand awareness, there has not been much research specifically examining how brand love is formed and to what extent these variables contribute to purchasing decisions for Generation Z in Eastern Indonesia, especially Jayapura City. The method used in this study is a quantitative method. The selected respondents were individuals included in the Generation Z category in Jayapura City. The results of the study indicate that brand love has a positive and significant influence on Oreo purchase decisions among Generation Z. This finding indicates that emotional closeness, interest, and positive experiences with the Oreo brand play an important role in driving purchasing decisions for Generation Z consumers in Jayapura City. The implications of the research indicate that companies need to strengthen emotional-based marketing strategies, create more interactive brand experiences, and strengthen images that are relevant to the identity of Generation Z. Thus, this research provides theoretical contributions in the development of consumer behavior studies as well as practical contributions for companies in designing strategies to maintain loyalty and improve purchasing decisions in local markets.